2021
DOI: 10.1007/s40891-021-00335-1
|View full text |Cite
|
Sign up to set email alerts
|

Dewatering Rate Saltation Problem in PHD-Treated Slurry and a Theoretical Explanation

Abstract: Prefabricated horizontal drains (PHD) exhibit lots of priority against vertical drains in treatment of high moisture slurry. However, recent research reported a significant dewatering rate saltation (DRS) problem in PHD-treated slurry, and theoretical explanation and quantitative analysis are lacking. This research first reanalyzed the recently reported tests of PHD-and flocculant-treated slurry, where the DRS problem was studied through water discharge rate and soil-water height difference (Δh). Then, a 1D co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, the fill materials placed on top of the layer of GHDs can now contribute to the surcharge preloading. A 1D consolidation solution was proposed by Zhou et al [23] considering the vacuum boundary and critical flow gradient.…”
Section: Horizontal Drain Vacuum Preloadingmentioning
confidence: 99%
“…Furthermore, the fill materials placed on top of the layer of GHDs can now contribute to the surcharge preloading. A 1D consolidation solution was proposed by Zhou et al [23] considering the vacuum boundary and critical flow gradient.…”
Section: Horizontal Drain Vacuum Preloadingmentioning
confidence: 99%
“…For these 11 papers [1][2][3][4][5][6][7][8][9][10][11] in this special issue, we would like to group them according to the ground improvement method being considered and then point out the key issue(s) investigated only in this editorial note. There are four articles dealt with new innovative techniques to increase efficiency of (vacuum) consolidation; four articles studied new technics of soft ground improvement using chemical/cement mixing method; one article studied replacement technique, one article investigated effects of microbial induced calcite precipitation on the strength and modulus of clays, and one article dealt with the site investigation using piezocone test for design of soft ground improvement.…”
mentioning
confidence: 99%
“…(1) Consolidation techniques Article 7:87 [4] experimentally studied the effect of air injection mode on the performance of air-booster vacuum consolidation and suggested a way of step-wise increase air pressure during the consolidation process. Article 7:93 [8] studied the vacuum dewatering of slurry using prefabricated horizontal drain (PHD) and proposed a method for predicting the variation of drainage rate from the PHD. Article 7:96 [10] investigated a field case history of combined vacuum pressure and embankment load induced consolidation with installation of prefabricated vertical drains (PVDs), and indicated that the existing design/analysis methods are valid and useful.…”
mentioning
confidence: 99%